2012
DOI: 10.5993/ajhb.36.3.9
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Change in Physical Activity and Disability in Adults

Abstract: Objectives To prospectively examine whether physical activity or change in physical activity increases or decreases the risk of disability later in life. Methods Tobit regression models were used to examine the effect of physical activity at baseline and change from baseline on disability 10 and 20 years later in 6913 adults. Results Increasing recreational physical activity was associated with reduced risk of disability whereas reducing recreational physical activity increased the risk of disability after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 35 publications
2
20
0
1
Order By: Relevance
“…being physically active, having a healthy diet, and not smoking), also reduce the likelihood of functional limitations and disability[8, 19, 22, 25, 27, 29, 30, 32, 33, 42, 44]. For example, in the National Health and Nutrition Examination Survey I and Epidemiologic Follow-Up Study, increased recreational physical activity (PA) over a period of 10 years resulted in reduced risk of disability, whereas reduced PA increased the risk[14]. Similarly, in a combined analysis of the Health and Retirement Study (HRS) and the Asset and Health Dynamics Among the Oldest Old (AHEAD) cohorts, current smoking was strongly related to impaired mobility[29], and in the Health ABC cohort, adherence to a Mediterranean diet was associated with less decline in walking speeds over 8 years[32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…being physically active, having a healthy diet, and not smoking), also reduce the likelihood of functional limitations and disability[8, 19, 22, 25, 27, 29, 30, 32, 33, 42, 44]. For example, in the National Health and Nutrition Examination Survey I and Epidemiologic Follow-Up Study, increased recreational physical activity (PA) over a period of 10 years resulted in reduced risk of disability, whereas reduced PA increased the risk[14]. Similarly, in a combined analysis of the Health and Retirement Study (HRS) and the Asset and Health Dynamics Among the Oldest Old (AHEAD) cohorts, current smoking was strongly related to impaired mobility[29], and in the Health ABC cohort, adherence to a Mediterranean diet was associated with less decline in walking speeds over 8 years[32].…”
Section: Introductionmentioning
confidence: 99%
“…To date, most of this literature is based on older [19, 25, 44], predominantly white populations[8, 29, 32, 42], focused on single health behaviors[8, 14, 22, 32, 42, 44] and/or reliant on self-reported measures of mostly mobility-related physical function, rather than objectively measured physical performance that includes more integrated measures of function[14, 19, 21, 25, 29]. The aim of the current study is to examine the individual and combined influence of participation in regular physical activity, consumption of a healthy diet, and abstinence from tobacco on subsequent performance-based measures of physical function during midlife, using data from the Study of Women Across the Nation (SWAN).…”
Section: Introductionmentioning
confidence: 99%
“…Previous longitudinal studies investigating the effect of changes in physical activity over a lifetime found increased physical activity is associated with reduced risk of disability. (25, 26) The recent LIFE randomized clinical trial demonstrated a structured physical activity intervention reduced mobility disability in older adults who were initially deemed at high risk for mobility disability. Over an average follow-up period of 2.6 years, 30.1% of participants in the intervention group vs 35.5% of controls experienced major mobility disability.…”
Section: Discussionmentioning
confidence: 99%
“…La tabla 1 describe detalladamente para cada participante los datos demográficos, tipo de discapacidad física, grado de independencia (información del servicio de medicina y fisioterapia del CRE) y nivel de actividad física, el cual se obtuvo preguntando: "en tu día habitual, aparte de la recreación, ¿eres físicamente muy activo, moderadamente activo o sedentario?" (Gretebeck, Ferraro, Black, Holland, y Gretebeck, 2012). La edad media (desviación estándar) de 52.6 (7.7) años superaba el punto de corte de 45 años planteado por Alcedo, Aguado, Arias, González, y Rozada (2008) como indicador de envejecimiento en sujetos con discapacidad.…”
Section: Participantesunclassified